Simulating Active Layer Thaw in a Boreal Environment - Woo, Ming-ko; Mollinga, Michael; Smith, Sharon (Géographie physique et Quaternaire, 2006)
AbstractA large part of the boreal zone of the western Canadian Arctic is underlain by ice-rich discontinuous permafrost which when thawed, can lead to settlement of the ground surface that has implications for the integrity of northern infrastructure, including oil and gas pipelines. A simple yet physically-based model is desired to simulate thawing of the active layer in different materials commonly found along the Mackenzie Valley pipeline corridor. Stefan’s algorithm determines the phase change of soil moisture using ground surface temperature as the upper boundary condition and conduction to transfer heat to the freeze-thaw front. It is tested on a permafrost site near Wrigley, Northwest Territories, where the computed thaw penetration compares satisfactorily with field data. To further explore the effects of climate and soil types on active layer depth, three representative sites in the Mackenzie valley where ground surface temperatures are available were selected for simulation of ground thaw, under two summer conditions. Results of the simulation demonstrate the sensitivity of active layer thaw to (1) soil materials due to differential thermal properties, (2) moisture content, which largely controls the latent heat requirement for phase change, and (3) inter-annual variations in ground surface temperature. Given the strong potential for environmental changes in the vast boreal region, the model allows the active layer thaw responses to be easily assessed.